Fabrication of Nickel NanoChains/PVDF Nanocomposites and Their Electrical/Magnetic Properties. Issue 16 (28th May 2019) - Martin, Baptiste; Dantras, Eric; Lonjon, Antoine; Laffont, Lydia; Lacabanne, Colette
Abstract : Magnetic nickel nanoparticles (NPs) and nanochains (NNCs) are grown in a polyol medium under a static field as an alternative to template electrodeposition and strong reducers. Scanning electron microscopy (SEM) images and their statistical analysis show an important aspect ratio of 75 for NNCs. These NNCs present enhanced magnetic properties in terms of coercive field ( H C  = 163 Oe) and saturation magnetization ( M S  = 10.8 emu g −1 ). Nanocomposites of NNCs/PVDF are fabricated with 2 %vol. NNCs and present better properties than NPs/PVDF with higher filler content. The longitudinal and transverse magnetic properties of the composite are measured showing that higher properties are recorded in the longitudinal direction. Electrical conductivity of composite is plotted as a function of NNCs volume content to determine the electrical percolation threshold. The corresponding value of the apparent aspect ratio (ξ = 70) confirms that the processing of composite does not modify the particles morphology. Thus, it explains the enhancement of the magnetic properties due to the NNCs anisotropy. Abstract : Nickel nanochains are fabricated with an aspect ratio of 75. Composites are successfully fabricated with 2 %vol NNCs. Good magnetic properties are obtained as M s  = 10.8 emu g −1 and H C  = 163 Oe. Above percolation threshold composites exhibit a transversal electrical conductivity of 50 S m −1 .